Vernacular Architecture: A Culturally Motivated and Interdisciplinary Literature Review - Ralwala, Anthony O. (Journal of the Kenya National Commission for UNESCO, 2023)
This study undertakes a critical literature review of purposively selected seminal publications on Kenyan culture as well as vernacular architecture in Kenya and South Africa. Content from other humanities disciplines like art, philosophy, history and literature are used to enrich architectural discourse, as interdisciplinary support which promotes hermeneutic interpretation. Cumulative hermeneutic explications will eventually yield the semiology of vernacular built forms through inter-subjectivity. The review highlights the focus, study approaches, achievements and positions of scholars on pertinent issues, and identifies lacunae for possible future investigations. A qualitative eco-systemic method is adopted together with a dialogic presentation method in the form of short direct quotes from the scrutinised publications. These quotes and the page numbers for citations are employed to portray the literature review as an ongoing verifiable debate within contemporary theoretical discourse. Though subjective, the critique in the study will hopefully generate or sustain debate on vernacular (and regional) architecture. This will yield more studies on the cultures of Kenyan indigenous communities in order to enhance scholarship on Kenyan vernacular architecture.